2021
DOI: 10.3390/rs13030457
|View full text |Cite
|
Sign up to set email alerts
|

UAV Data as an Alternative to Field Sampling to Monitor Vineyards Using Machine Learning Based on UAV/Sentinel-2 Data Fusion

Abstract: Pests and diseases affect the yield and quality of grapes directly and engender noteworthy economic losses. Diagnosing “lesions” on vines as soon as possible and dynamically monitoring symptoms caused by pests and diseases at a larger scale are essential to pest control. This study has appraised the capabilities of high-resolution unmanned aerial vehicle (UAV) data as an alternative to manual field sampling to obtain sampling canopy sets and to supplement satellite-based monitoring using machine learning model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 82 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…The impact of data fusion varies with the type of application. Studies that focused on the fusion of digital images invariably showed improvements with respect to the results obtained using single data sources [ 18 , 19 , 39 , 84 , 99 , 106 ], although in some cases the improvement may not be substantial enough to justify the capture of additional data [ 21 , 71 ]. The success of data fusion applied to digital images can be linked not only to the complementarities shown by different types of images, but also to the fact that the images can be easily made compatible using simple normalization operations when needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of data fusion varies with the type of application. Studies that focused on the fusion of digital images invariably showed improvements with respect to the results obtained using single data sources [ 18 , 19 , 39 , 84 , 99 , 106 ], although in some cases the improvement may not be substantial enough to justify the capture of additional data [ 21 , 71 ]. The success of data fusion applied to digital images can be linked not only to the complementarities shown by different types of images, but also to the fact that the images can be easily made compatible using simple normalization operations when needed.…”
Section: Discussionmentioning
confidence: 99%
“…In their work, the model was tested using data collected in a different year, under the justification that validating a model with data captured under very similar conditions to those used for training will almost invariably lead to unrealistic results, which unfortunately is usually the case. Indeed, when this approach was applied by Zhou et al [ 71 ], the results obtained for different years were strongly disparate, thus revealing that the data used for training was not representative enough. Veum et al [ 36 ] added that it is difficult to find the ideal sample distribution due to too much homogeneity and presence of extraneous factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple linear regression (MLR) is a statistical technique that predicts the outcome of a dependent variable using multiple independent variables. The RF Regression is a supervised learning approach for regression that uses the ensemble learning technique for remote sensingbased agricultural research projects [17,37]. The decision tree (DT) uses a tree topology to generate regression or classification models.…”
Section: Machine Learning For Crop Health and Chlorophyll Contentmentioning
confidence: 99%
“…ML technologies have been used to predict crop parameters [37]. For example, winter wheat biomass estimation was carried out using the visualization approach for SVR and the investigation of influential textures [39].…”
Section: Machine Learning For Crop Health and Chlorophyll Contentmentioning
confidence: 99%